Active and latent tuberculosis among HIV-positive injecting drug users in Indonesia - Meijerink, Hinta (J Int AIDS Soc, 2015)
INTRODUCTION: Injecting drug use (IDU) is associated with tuberculosis but few data are available from low-income settings. We examined IDU in relation to active and latent tuberculosis (LTBI) among HIV-positive individuals in Indonesia, which has a high burden of tuberculosis and a rapidly growing HIV epidemic strongly driven by IDU. METHODS: Active tuberculosis was measured prospectively among 1900 consecutive antiretroviral treatment (ART)-naïve adult patients entering care in a clinic in West Java. Prevalence of LTBI was determined cross-sectionally in a subset of 518 ART-experienced patients using an interferon-gamma release assay. RESULTS: Patients with a history of IDU (53.1%) more often reported a history of tuberculosis treatment (34.8% vs. 21.9%, p<0.001), more often received tuberculosis treatment during follow-up (adjusted HR=1.71; 95% CI: 1.25–2.35) and more often had bacteriologically confirmed tuberculosis (OR=1.67; 95% CI: 0.94–2.96). LTBI was equally prevalent among people with and without a history of IDU (29.1 vs. 30.4%, NS). The risk estimates did not change after adjustment for CD4 cell count or ART. CONCLUSIONS: HIV-positive individuals with a history of IDU in Indonesia have more active tuberculosis, with similar rates of LTBI. Within the HIV clinic, LTBI screening and isoniazid preventive therapy may be prioritized to patients with a history of IDU.